Percepções da alteridade na visualidade contemporânea : como nos posicionamos diante do outro em situações distantes da nossa - Rangel, Valeska Bernardo (2018)
We report experiences on Visual Arts teaching, carried out with classes of the Technical Courses Integrated to High School, at Instituto Federal de Santa Catarina (IFSC), Brazil. The purpose is to investigate how we stand in front of images of the Other in situations far from ours, beyond compassion and detachment. From the images of the Other chosen by the students, we instigated a dialogue in order to disturb our accommodated and generally prejudiced gazes, bringing up questions such as alterity, construction of gazes, awareness of affections, etc.